The reality of the use of electronic blogging in the educational process from the point of view of teachers during psychological and social studies for the secondary stage in Makkah - Al-Zahrani, Shroog Salem (Journal of Curriculum and Teaching Methodology, 2024)
The aim of this study to reveal the reality and obstacles to the use of electronic multimedia blogging in the educational process from the point of view of the teachers during psychological and social studies of the secondary stage in Makkah. The researcher followed the descriptive analytical method by collecting the study data using the questionnaire, which consisted of (22) paragraphs distributed on two axes, namely first: the reality of using electronic multimedia blogging and second: the obstacles to the use of electronic blogging multiple. If it was applied to a random sample of (50) female teachers of the psychological and social studies course. The results of the data analysis revealed a high overall average score for applying multimedia electronic blogging with female secondary school students from the teachers’ point of view. The results also showed that the arithmetic mean for the obstacles axis was (3.69), which indicates the presence of obstacles that limit the use of electronic blogging with female students, represented by: The lack of training courses for teachers to design and produce electronic blogs, and the lack of specialists in designing and producing electronic blogs limits their benefit in teaching female students at the secondary level.